Unexpected Imidazoquinoxalinone Annulation Products in the Photoinitiated Reaction of Substituted‐3‐Methyl‐Quinoxalin‐2‐Ones with N‐Phenylglycine1. (4th November 2013) - De la Fuente, Julio R.; Cañete, Álvaro; Jullian, Carolina; Saitz, Claudio; Aliaga, Christian
Abstract: Photoinduced electron transfer between N ‐phenylglycine (NPG) and electronically excited triplets of 7‐substituted‐3‐methyl‐quinoxalin‐2‐ones in acetonitrile generate the respective ion radical pair, where by decarboxylation the phenyl‐amino‐alkyl radical, PhNHCH2, is generated. This radical reacts with the 3‐methyl‐quinoxalin‐2‐ones ground states, leading to the product 2. Other, unexpected, 7‐substituted‐1, 2, 3, 3a‐tetrahydro‐3a‐methyl‐2‐phenylimidazo[1, 5‐a]quinoxalin‐4(5 H )‐ones, annulation products, 3a–f, were generated; likely by the addition of two PhNHCH2 radicals, to positions 3 and 4 of the quinoxalin‐2‐ones. The reaction mechanism includes a photoinduced one electron transfer initiation step, propagation steps involving radical intermediates and NPG with radical chain termination steps that lead to the respective products 2a–f and 3a–f and NPG by‐products. The proposed mechanism accounts for the strong dependency found for the initial photoconsumption quantum yields on the electron‐withdrawing power of the substituent. Therefore, photolysis of common reactants widely used such as NPG and substituted quinoxalin‐2‐ones may provide a simple synthetic way to the unusual, unreported tetrahydro‐imidazoquinoxalinones 3a–f. Abstract : Photoinduced electron transfer between N ‐phenylglycine (NPG) and electronically excited triplets of 7‐substituted‐3‐methyl‐quinoxalin‐2‐ones generate the unexpected, 7‐substituted‐1, 2, 3, 3a‐tetrahydro‐3a‐methyl‐2‐phenylimidazo[1, 5‐a]quinoxalin‐4(5 H )‐ones, annulation products. A reaction mechanism includes a photoinduced single electron transfer initiation step, propagation steps involving radical intermediates and NPG, with radical chain termination steps, leads to the respective products and NPG by‐products.